FRI0038 HERPES ZOSTER IN RHEUMATOID ARTHRITIS. PROSPECTIVE SINGLE CENTER STUDY OF 390 RA PATIENTS FOR 5YEARS. (June 2019) - Domínguez, Lucia; Calvo-Río, Vanesa; Rodriguez-Cundin, Paz; Portilla, Virginia; Vegas-Revenga, Nuria; Antolin-Juarez, Francisco Manuel; Antolin-Juarez, Francisco Manuel; Corrales, Alfonso; Prieto-Peña, D.; Calderón-Goercke, Monica; González-Gay, Miguel A.; Blanco, Ricardo
Abstract : Background: Immunosuppressed patients such as Rheumatoid Arthritis (RA) patients have a greater risk (1.5-2 times) of presenting herpes zoster (HZ). Both, the disease itself and the use of immunosuppressive drugs, are involve in this increased risk. Furthermore, in these patients is more frequent a disseminated presentation of zoster involving several dermatomes. Objectives: In a series of RA patients our aim was analyzed HZ infections and to assess a) HZ prevalence and b) HZ general features Methods: Prospective Single center study of 390 RA patients included in the vaccination program of the Preventive and Rheumatology department of our hospital between october 2011 and october 2016. The follow-up was made until December 2017. HZ vaccination is not included in our program. RA was diagnosed according to the ACR/EULAR 2010 proposed criteria (Arthritis Rheum 2010; 62: 2569–2581) The diagnose of HZ was made according to the clinical manifestations and was confirmed by a dermatologist. These manifestations were characteristic skin rash and blisters, paresthesia and local pain, in one (localized) or more dermatomes (generalized) Results: We studied 390 patients (307♀/83♂), average age 61.28±12.9 years that were included in the vaccination program and followed-up. HZ infection was observed in 12 of 390 (3.07%) in the follow-up (TABLE). The 12 RA patients (11 women/1 man) with a mean±SD age of 67.5±11.67. More than half of patients, 7 (58.33%) were taking corticosteroids. 8 patients (66.66%) were receiving conventional disease modifying drugs (DMARDs) methotrexate (33.33%), leflunomide (16.66%) and hydroxychloroquine (16.66%). Besides corticosteroids and conventional DMARDs, 7 patients (58.33%) were in treatment with biologic drugs, tocilizumab (n=2), etanercept (n=2), adalimumab (n=2), and rituximab (n=1). Conclusion: Herpes zoster is a relative frequent viral infection in RA patients non-vaccine for HZ. The female sex, older age, more aggressive RA and treatment with corticosteroids were more frequent. Probably in this group of patients HZ vaccination may be useful. Abbreviatures: MTX: methotrexate, LFN: leflunomide, HCQ: hydroxicloroquine, TCZ: tocilizumbas, ADA: adalimumab, ETN: etanercept Disclosure of Interests: Lucia Domínguez: None declared, Vanesa Calvo-Río: None declared, Paz Rodriguez-Cundin: None declared, Virginia Portilla: None declared, Nuria Vegas-Revenga: None declared, Francisco Manuel Antolin-Juarez: None declared, Maria Henar Rebollo Rodriguez: None declared, Alfonso Corrales: None declared, D. Prieto-Peña: None declared, Monica Calderón-Goercke: None declared, Miguel A González-Gay Grant/research support from: Prof. MA Gonzalez-Gay received grants/research supports from Abbvie, MSD, Jansen and Roche., Speakers bureau: Consultation fees/participation in company sponsored speaker's bureau from Pfizer, Lilly, Sobi, Celgene, Novartis, Roche and Sanofi., Ricardo Blanco Grant/research support from: Abbvie, MSD, and Roche, Consultant for: Abbvie, Pfizer, Roche, Bristol-Myers, Janssen, Speakers bureau: Abbvie, Pfizer, Roche, Bristol-Myers, Janssen